Wnt-3, a gene activated by proviral insertion in mouse mammary tumors, is homologous to int-1/Wnt-1 and is normally expressed in mouse embryos and adult brain. - Roelink, H (1990)
We have isolated a common insertion site, Wnt-3, for proviruses of the mouse mammary tumor virus (MMTV). Of mammary tumors induced by the GR variant of MMTV, 5% contains a provirus at Wnt-3, which is located on mouse chromosome 11. The gene is transcribed into a 3.8-kilobase (kb) mRNA in tumors with nearby proviral insertions but not in tumors with proviruses at other loci or in most adult tissues. Normal expression of Wnt-3 is detected in mouse embryos (with a peak around day 12 of gestation) and at low levels in adult brain. The transcriptional unit of the Wnt-3 gene spans approximately 55 kb, with a first intron of 36 kb. The deduced amino acid sequence of the Wnt-3 protein is 47% identical to the int-1/Wnt-1 gene product.